“TEMANTA”KELOMPOK PENDAMPING TEMAN SEBAYA DALAM UPAYA PENCEGAHAN KEHAMILAN PRANIKAH REMAJA - Jamir, A.Fatimah; lindriani, lindriani; Rosdiana, Rosdiana (Jurnal Abdi Insani, 2024)
Premarital pregnancy is a pregnancy that is generally unplanned and gives rise to feelings of guilt, sin and shame in teenagers who experience it, coupled with social sanctions from society against pregnancy and the birth of children without marriage. Early pregnancy increases the mortality rate for babies and mothers under 18 years of age. The reason is, a young teenager is at greater risk of dying during pregnancy and childbirth than women aged 20 years and over. The aim of this community service is to form a "Temanta" group to accompany peers as an effort to prevent teenage premarital pregnancy. Conduct a pretest first on students to find out students' knowledge, then conduct counseling with material about efforts to prevent premarital pregnancy in teenagers and after that carry out a posttest. The next activity is to conduct peer mentoring training for students by improving students' skills in communication and peer counseling. And the final activity is the formation of a peer mentoring group called "TEMANTA". The results of the Wilcoxon test showed that there were differences in students' knowledge and skills before and after treatment with a p value of 0.001<0.005, and the formation of the "TEMANTA" group at Satap Salusimbuang Middle School, Luwu Regency. The formation of the "TEMANTA" group can be useful in peer mentoring students in efforts to prevent premarital pregnancy in teenagers.